"At a loss of what to do": a qualitative analysis of parents' online discussion forums about their administration of asthma inhalers to their young children. (2nd August 2020) - Law, Gloria C.; Jones, Christina J.; Bülbül, Alpaslan; Smith, Helen E.
Abstract: Objective: The difficulties adults have using inhaler devices is well documented but much less is known about how parents administer inhaler devices to young children and the difficulties experienced. The purpose of this article is to explore the underlying concepts and practical issues that parents encounter in administering inhaled asthma medications to their young children. Methods: This is a qualitative study using applied thematic analysis on parental written discourses from asynchronous online discussion forums on the topic of administration and use of asthma inhaler devices to young children. Results: "At a loss of what to do" summarizes the experiences parents described when administering inhaler devices to their young children. Parents describe the problems, the situations, the emotions, the decisions, and the confusion they face. They struggle with their child's resistance and the associated conflict, describing their own and their child's distress. Results highlight the coping strategies used in administration, how parents decide whether to use coercive measures or not, their help-seeking endeavors, together with the assurance they give to themselves and others after administration. Conclusion: The online discussions highlight parents' distress, lack of preparedness, and understanding of administering inhaler devices to young children. While the prevalence of the problem cannot be estimated from our data, it illustrates a need for some healthcare professionals to review their own knowledge and skills in administration of inhaled medication to younger patients, and their provision of patient and family centered care.